Identification of a group of brominated flame retardants as novel androgen receptor antagonists and potential neuronal and endocrine disrupters. (January 2015) - Kharlyngdoh, Joubert Banjop; Pradhan, Ajay; Asnake, Solomon; Walstad, Anders; Ivarsson, Per; Olsson, Per-Erik
Abstract: Brominated flame-retardants (BFRs) are used in industrial products to reduce the risk of fire. However, their continuous release into the environment is a concern as they are often persistent, bioaccumulating and toxic. Information on the impact these compounds have on human health and wildlife is limited and only a few of them have been identified to disrupt hormone receptor functions. In the present study we used in silico modeling to determine the interactions of selected BFRs with the human androgen receptor (AR). Three compounds were found to dock into the ligand-binding domain of the human AR and these were further tested using in vitro analysis. Allyl 2, 4, 6-tribromophenyl ether (ATE), 2-bromoallyl 2, 4, 6-tribromophenyl ether (BATE) and 2, 3-dibromopropyl-2, 4, 6-tribromophenyl ether (DPTE) were observed to act as AR antagonists. These BFRs have recently been detected in the environment, in house dust and in aquatic animals. The compounds have been detected at high concentrations in both blubber and brain of seals and we therefore also assessed their impact on the expression ofL -type amino acid transporter system (LAT) genes, that are needed for amino acid uptake across the blood–brain barrier, as disruption of LAT gene function has been implicated in several brain disorders. The three BFRs down-regulated the expression of AR target genes that encode for prostate specific antigen (PSA), 5 α- reductases and β-microseminoprotein. The potency of PSA inhibition was of the same magnitude as the common prostate cancer drugs, demonstrating that these compounds are strong AR antagonists. Western blot analysis of AR protein showed that ATE, BATE and DPTE decreased the 5 α- dihydrotestosterone-induced AR protein levels, further confirming that these BFRs act as AR antagonists. The transcription of the LAT genes was altered by the three BFRs, indicating an effect on amino-acid uptake across cellular membranes and blood–brain barrier. This study demonstrated that ATE, BATE and DPTE are potent AR antagonists and the alterations in LAT gene transcription suggest that these compounds can affect neuronal functions and should be considered as potential neurotoxic and endocrine disrupting compounds. Highlights: ATE, BATE and DPTE are potent androgen receptor antagonists. ATE, BATE and DPTE destabilized DHT-induced androgen receptor proteins. ATE, BATE and DPTE altered LAT gene transcript levels. ATE, BATE and DPTE are potential neuronal and endocrine disruptors.